1980
DOI: 10.4319/lo.1980.25.1.0001
|View full text |Cite
|
Sign up to set email alerts
|

Availability to Scenedesmus quadricauda of different forms of phosphorus in sedimentary materials from the Great Lakes1

Abstract: Sedimentary materials from eroding bluffs, suspended solids in streams, and lake bottom sediments from Lakes Ontario and Erie were cultured with the alga Scenedesmus quadricauda (Turp.) de Brebisson in modified Rodhe's medium with the sediments as the sole source of P. P uptake by the algae was related to the amount of nonapatite inorganic phosphorus in the sediments. Apatite phosphorus was not used, and the bluff samples, in which over 90% of total P was in this form, did not support algal growth. The nonapat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0
3

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(125 citation statements)
references
References 17 publications
(17 reference statements)
2
120
0
3
Order By: Relevance
“…Fe-P is considered to be an easily resolved constituent of sediments, since it may vary with the change of environmental redox conditions (Samadi-Maybodi et al, 2013;Zhuang et al, 2014). Au-P and De-P have a minor contribution to the accumulation of P in the sediment pore water or overlying water due to their low activities in the weak alkaline aquatic environment (Sagher et al, 1975;Williams et al, 1980;Andrieux and Aminot, 1997). OP is a bio-available form of P (Ruban et al, 2001), because it is biogeochemically active and could mineralize easily to primary producers' usable forms of P (Andrieux and Aminot, 1997;Zhuang et al, 2014).…”
Section: Organic Pmentioning
confidence: 99%
“…Fe-P is considered to be an easily resolved constituent of sediments, since it may vary with the change of environmental redox conditions (Samadi-Maybodi et al, 2013;Zhuang et al, 2014). Au-P and De-P have a minor contribution to the accumulation of P in the sediment pore water or overlying water due to their low activities in the weak alkaline aquatic environment (Sagher et al, 1975;Williams et al, 1980;Andrieux and Aminot, 1997). OP is a bio-available form of P (Ruban et al, 2001), because it is biogeochemically active and could mineralize easily to primary producers' usable forms of P (Andrieux and Aminot, 1997;Zhuang et al, 2014).…”
Section: Organic Pmentioning
confidence: 99%
“…The non-apatite inorganic P fraction was highly correlated with the amounts of inorganic P extracted by three techniques for estimating "available P" and cell uptake equaled NaOH-extractable inorganic P in several instances. Organic P in the sediments was not utilized by the algae (Williams et al, 1980). Interest in organic P was, however, renewed with the use of 31 P NMR spectroscopy since the 1980s.…”
Section: Ecological Interpretation Of Operationally Defined P Fractionsmentioning
confidence: 99%
“…They therefore suggested several modifications (Williams et al, 1967;1976) as indicated in Table 1. Williams et al (1976Williams et al ( , 1980 used an extraction method with CDB (tri-sodium citrate, sodium dithionite and sodium bicarbonate) followed by NaOH. A subsequent extraction with HCl is supposed to extract Ca-P.…”
Section: Williams Methodsmentioning
confidence: 99%
See 2 more Smart Citations